Disaster Resilience Reduces Radiation-Related Anxiety Among Affected People 10 Years After the Fukushima Daiichi Nuclear Power Plant Accident - Kobayashi, Tomoyuki; Maeda, Masaharu; Nakayama, Chihiro; Takebayashi, Yui; Sato, Hideki; Setou, Noriko; Momoi, Maho; Horikoshi, Naoko; Yasumura, Seiji; Ohto, Hitoshi (Frontiers in Public Health, 2022)
This study examined whether disaster resilience affects the recovery of mental health states and mitigates psychosocial anxiety 10 years later the Fukushima Daiichi nuclear power plant accident. The survey was conducted in Fukushima's evacuation-directed and non-evacuation-directed areas in January 2020. The 695 participants responded to a questionnaire including items on radiation-related anxiety regarding the Fukushima Daiichi accident, an action-oriented approach as a resilience factor, psychological distress, and demographic information. The structural equation modeling showed that the action-oriented approach also eased radiation-related anxiety by mediating with improving mental health states. Moreover, a multi-group model analysis was conducted for evacuation-directed and non-directed areas. In the evacuation-directed area, we found stronger associations among resilience, mental health states, and radiation-related anxiety, and a direct effect of resilience factors on radiation risk anxiety. These findings emphasize the importance of resilience in post-disaster contexts, at least for a decade, where mental health deteriorates and various psychosocial issues become more complex.